1999
DOI: 10.1046/j.1440-1614.1999.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of First Presentation Psychosis in Old Age

Abstract: The descriptive findings in this study suggest that psychosocial factors require further investigation in patients presenting with late-onset psychosis. Comparison with younger first-onset psychotic subjects will be the subject of a later report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, in most studies, negative symptoms were absent in VLOSLP [14,20] while they were present in EOS and to a lesser extent in LOS [14]. Negative symptoms were not at all or barely mentioned in several studies on VLOSLP [18,21,24,26].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, in most studies, negative symptoms were absent in VLOSLP [14,20] while they were present in EOS and to a lesser extent in LOS [14]. Negative symptoms were not at all or barely mentioned in several studies on VLOSLP [18,21,24,26].…”
Section: Introductionmentioning
confidence: 92%
“…In terms of sociodemographics, there was generally a female preponderance in VLOSLP [1,14,18,20,22,[24][25][26]29]. Regarding education, in one instance patients with VLOSLP were described as being more educated than elderly EOS [26] but in another study they were reported to be less educated than LOS [25].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations